Os impactos da mudança climáticas na saúde e os desafios das políticas públicas atuais - Sousa, Leta Vieira de (2024)
This dissertation aims to analyze the impacts of climate change on health from a public policy perspective. Climate change is one of the greatest challenges of the 21st century, with comprehensive and multifaceted impacts that affect various sectors of society, including public health. However, public health is still underrepresented in climate- related research and specialized public policy. As a result, there is a growing number of people who die or suffer from prolonged illnesses with each extreme weather event. These impacts are not limited to extreme events but also affect the daily lives of city dwellers, where climate change is already present and causing various types of diseases. To increase resilience and adaptation to the health impacts of climate change, this research aims to contribute to climate public policies, especially Climate Action Plans, to also drive improvements in the health of city residents in the context of climate change. Through tools such as Systematic Literature Review and documentary analysis, it was possible to generate an overview capable of contributing to public policies that mitigate the health impacts of climate change, especially considering the population with greater social vulnerability. The results include creating a unique overview that brings together the main health impacts of climate change in Global South countries and contributing to the enhancement and improvement of the health component in Climate Action Plans. In conclusion, the relevance of more in-depth studies on the topic is highlighted, as well as its importance from the perspective of necessary complementation for public policies that contribute to increased resilience and adaptation of public health.